Techno-economic evaluation of grid connected PV system for households with feed in tariff and time of day tariff regulation in New Delhi – A sustainable approach. (April 2017) - Tomar, Vivek; Tiwari, G.N.
Abstract: With growing demand of electricity and continuously receding the natural resource have made inevitable look toward renewable energy resource. Moreover, the photovoltaic technology is advance and emerging technology. This paper discuss the feasibility of grid connected Roof-top/Building integrated photovoltaic (BIPV) system for the electrification of consumption wise three different residential households with incorporating feed in tariffs/ net metering process along with Tariff of day (ToD) tariff regulation in the New Delhi, India. HOMER has been used to carry out the techno-economic evaluation of grid connected photovoltaic (PV) system. The simulation indicates that the cost of energy (COE)) and Net Present Cost (NPC) become 0 at around 1.8 kW and 3.4 kW for low and middle slab household. Moreover, high slab demand households required large infrastructure and greater capital to obtain effective results. The results clearly identify that feed in tariff/net metering and time of day (ToD) tariff regulation are majorly impact on low and middle slab households rather than high slab households. It has been observed that COE is continuously decreased with capacity addition as well as linearly increase with battery storage independent of power consumption. It concluded that grid connected solar PV system without battery storage is both technically and economically viable option for decentralized roof-top/BIPV application. This study also takes into account the possible scenario of carbon emission reduction.